고혈압 환자에서 불안증상에 영향을 미치는 정신심리학적 요인 - 문석현; 김승곤; 양혜정; 서은현; 윤형준; Moon, Seock Hyeon; Kim, Seung-Gon; Yang, Hae-Jung; Seo, Eun Hyun; Yoon, Hyung-Jun (Anxiety and mood, 2022)
Objective : The aim of this study was to investigate the prevalence of anxiety symptoms and its association with psychological factors in patients with hypertension. Methods : The Participants included 124 patients with hypertension. Anxiety symptoms were evaluated by the Hospital Anxiety and Depression Scale. Socio-demographics, perceived stress, state-trait anger, life satisfaction, and ego resiliency were assessed. Stepwise multiple regression analyses were carried out to examine the impact of perceived stress, state-trait anger, and life satisfaction on anxiety symptoms. In addition, moderated regression analysis was performed to explore the moderating effect of ego resiliency between perceived stress and anxiety symptoms. Results : A total of 17 subjects (13.7%) were identified as having anxiety symptoms. Higher perceived stress and state-trait anger, and lower life satisfaction were found to be significant correlates of anxiety symptoms. In the final model, higher levels of perceived stress (β=0.378, p<0.001) and trait anger (β=0.320, p<0.001) were related to higher levels of anxiety symptoms, while a higher level of life satisfaction (β=-0.166, p=0.025) was associated with a lower level of anxiety symptoms. Further, ego resiliency buffered the negative effect of perceived stress on anxiety symptoms. Conclusion : This study demonstrated the prevalence of anxiety symptoms and associated psychological factors among patients with hypertension. Our findings suggest that improving life satisfaction and ego-resiliency as well as controlling stress and anger may be important in the management of anxiety symptoms in patients with hypertension.